Semotic Semiotic Analysis of “Super Reader” in “I Wandered Lonely as a Cloud” Poem by William Wordsworth - Gilang Bintang; Encep Rustandi; Reza Paramarta (Faculty of Language and Literature, University of Surakarta, 2023)
ABSTRACT This study aims to analyze the figure of speech in the poem “I Wandered Lonely as a Cloud” by William Wordsworth. The study's design is descriptive qualitative with no changes in the variables. It described the result of the semiotic analysis of the poetry “I Wandered Lonely as a Cloud”. The research technique has been done by using the super reader theory of analysis by Michael Riffaterre which focuses on three concepts: displacing, distorting, and creating. The result of the analysis shows that William Wordsworth’s poem represents super reader theory. Displacing the meaning of semiotic Super Reader reveals figurative language such as metaphor, personification, simile, and synecdoche. The figurative language revealed by the displacing and distorted meaning shows how the reflection of solitudes is described and his view on the sound of crowded society in the romantic age. This creates meaning when he feels lonely, angry, and alienated from it. The figurative language of metaphor has more dominance in this poem that relates to distorting meaning that some phrases or clauses have ambiguity, contradiction, and nonsense.